2018
DOI: 10.12691/jfe-6-2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Government Borrowing on Private Investments in Kenya

Abstract: This study analyzes the effect of government domestic borrowing on private investment using Gross fixed capital formation as a dependent variable. The study uses the data from 1975 to 2014 of Domestic debt, financial development, gross domestic savings, real interest rate and GDP per capita. The Auto Regressive Distributed Lag (ARDL) technique was used to find the long-run and short-run Co-integration relationship of the model between the independent variables and Gross fixed capital formation. Stability funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 11 publications
3
16
0
Order By: Relevance
“…To sum up, the findings on the presence of asymmetry in the relationship between private investment and public debt are in line with the literature that studies non-linear relationship between the two variables (see, e.g., Ebi & Imoke, 2017). Both long-run and short-run results suggest that higher public debt crowds out private investment, which is in line with the crowding-out effect hypothesis and empirical studies in China (Huang et al, 2016), advanced and emerging economies (Huang et al, 2018), Kenya (King'wara, 2014;Lidiema, 2018), OECD countries (Salotti & Trecroci, 2012), and Egypt (Shetta & Kamaly, 2014). Higher public debt may increase cost of borrowing for private investment through two ways.…”
Section: Empirical Analysissupporting
confidence: 74%
“…To sum up, the findings on the presence of asymmetry in the relationship between private investment and public debt are in line with the literature that studies non-linear relationship between the two variables (see, e.g., Ebi & Imoke, 2017). Both long-run and short-run results suggest that higher public debt crowds out private investment, which is in line with the crowding-out effect hypothesis and empirical studies in China (Huang et al, 2016), advanced and emerging economies (Huang et al, 2018), Kenya (King'wara, 2014;Lidiema, 2018), OECD countries (Salotti & Trecroci, 2012), and Egypt (Shetta & Kamaly, 2014). Higher public debt may increase cost of borrowing for private investment through two ways.…”
Section: Empirical Analysissupporting
confidence: 74%
“…In Kenya [21] using data from 1975 to 2014 empirical confirmed that excessive domestic borrowing by the government negatively affect investment by the private sector. Using panel data from 60 developing countries [12] provided evidence that there is a significant crowding out effect of government borrowing on private credit in these countries.…”
Section: Evidence From Other Countriesmentioning
confidence: 92%
“…As such, loanable funds theory strengthens the fact that conventional factors of real interest rates, private sector credit availability, and past economic growth influence the behavior of investments according to Ames et al (n.d.). Government domestic borrowing to finance public expenditure affects loanable funds available for private domestic investments (Lidiema, 2017). On the other hand, a decline from private domestic investments in Kenya from 1.3 points to 0.3 points of GDP was due to government fiscal expansion (World Bank report (2018)).…”
Section: Loanable Funds Theorymentioning
confidence: 99%